2014
DOI: 10.1097/igc.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Web-based Recruiting for a Survey on Knowledge and Awareness of Cervical Cancer Prevention Among Young Women Living in Kanagawa Prefecture, Japan

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 14 publications
2
29
0
Order By: Relevance
“…Haines-Saah et al [29] recruited 28% of participants via social media and 28% of participants via friend referral. Miyagi et al [30] recruited 52% of participants through Facebook and 48% via a website. The studies by Martinez et al [22] and Haines-Saah et al [29] were both interventional studies, whereas the study by Miyagi et al [30] was an observational study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Haines-Saah et al [29] recruited 28% of participants via social media and 28% of participants via friend referral. Miyagi et al [30] recruited 52% of participants through Facebook and 48% via a website. The studies by Martinez et al [22] and Haines-Saah et al [29] were both interventional studies, whereas the study by Miyagi et al [30] was an observational study.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, 13 studies targeted local regions within a country [15,18,22,23,26,27,30,33-35,37,40,42], 8 studies [14,19,28,31,35,38,39,41] targeted recruitment nationally, and 2 studies targeted recruitment internationally [16,36]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high HPV vaccination uptake among adolescent girls has already reduced high-grade cervical abnormalities among young women in Scotland [27]. Our recent study showed a much lower HPV vaccination uptake among young Japanese women than among Australian women [28]. With suspension of HPV vaccination in Japan, there is a concern that Japan's CC policy is running counter to the global trends of CC control.…”
Section: Discussionmentioning
confidence: 96%